2017
DOI: 10.1111/acem.13311
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Preliminary Clinical Outcomes of a Pharmacist‐managed Venous Thromboembolism Clinic for Patients Treated With Rivaroxaban Post Emergency Department Discharge

Abstract: Abstract:Objective. To describe the implementation, work flow, and differences in outcomes between a pharmacist-managed clinic for the outpatient treatment of venous thromboembolism (VTE) using rivaroxaban versus care by a primary care provider.Interventions. Patients in the studied health system that are diagnosed with low-risk VTE in the emergency department are often discharged without hospital admission. These patients are treated with rivaroxban and follow up either in a pharmacist-managed VTE clinic or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…results enriched the reported literature on the impact of clinical pharmacist care on individual components of anticoagulation therapy (Ashjian et al, 2017;DiRenzo et al, 2018). This study indicated that as part of the healthcare provider team, pharmacists are well-positioned to provide motivational advice and patient counseling to promote patient understanding of anticoagulation therapy, patient awareness of potential adverse events, and the importance of medication adherence during the epidemic period.…”
Section: Discussionmentioning
confidence: 52%
“…results enriched the reported literature on the impact of clinical pharmacist care on individual components of anticoagulation therapy (Ashjian et al, 2017;DiRenzo et al, 2018). This study indicated that as part of the healthcare provider team, pharmacists are well-positioned to provide motivational advice and patient counseling to promote patient understanding of anticoagulation therapy, patient awareness of potential adverse events, and the importance of medication adherence during the epidemic period.…”
Section: Discussionmentioning
confidence: 52%
“…This left 21 real-world studies evaluating clinical characteristics associated with or programs designed to facilitate outpatient DVT treatment to be included in our systematic review (Table 1). 4,8 -10,14 -37…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies of programs aimed at facilitating outpatient treatment of acute DVT for patients presenting to the ED identified in our systematic review, one (Beam and colleagues) reported outcomes among outpatients (n = 71) that were prospectively followed for ∼1 year (mean = 389 days) after their acute DVT. 8-9,35 -37 None of these patients had recurrent VTE or major bleeding while receiving DOAC therapy. Decreased costs and favorable health-related quality of life scores have also been reported among patients selected for outpatient treatment using the criteria described by Beam and colleagues.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations